Tracing the footprints of digital aggression: an ethnographic journey into cyber harassment against female activists in Bangladesh - Fatema, Ummul Khayer (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2023.